Post-secondary aspiration differences among upper secondary students: a descriptive comparison between selected vocational and public schools in Malaysia - Kamalludeen, Rosemaliza (2015)
The Malaysian government has placed increased emphasis on technical and vocational education (TVET) at the secondary level in the tenth Malaysia Plan (2011-2015). As such, over the past three years, technical/vocational education and training (TVET) in Malaysia has gone through a transformation exercise, more specifically the migration from Sekolah Menengah Teknik dan Vokasional (Vocation and Technical Secondary Schools) to Kolej Vokasional (Vocational College). However, TVET is still seen as a second option to general public schools due to stigma associated with skill-based education and poor academic achievement. In relation to the TVET transformation effort, this study attempted to investigate the differences between public school and vocational school students in selected Malaysian schools, in terms of their post-secondary plans. Through this study, the possibilities of curriculum choice influence on their post-secondary aspirations will be explored. Students' perspectives on how their schooling experiences coincide with their projection of potential post-secondary paths will be explored, and whether vocational education will be appealing to students at various levels of academic achievement. This study takes on a case-study approach and utilizes a mixed-methods design, including correlations and focus group interviews. The findings from this study will help explore more possibilities in the replication of the study nationwide, as well as to provide a preliminary output to the TVET transformation exercise by the Ministry of Education Malaysia. The results may also be utilised to increase public awareness and involvement in TVET in order to fulfill the needs of Malaysian skilled workforce.